Choosing a batch mixer - Fairchild, Fred J. (My University, 2015)
Once all of the ingredients have been weighed up in the proper amounts, the next step in the feed manufacturing process is to blend them together. This is done using some type of mixing apparatus. In this article we will look at different types of batch mixers used in the commercial and integrated feed industries.
Keywords: Feed processing; Horizontal mixers; Vertical mixers; Drum mixers